From one to one hundred - Sloat, Teri. ([New York : Dutton Children's Books, 1995)
Illustrations of people and animals introduce the numbers one through ten, followed by counting by tens, from 20 to 100.
"A Puffin unicorn.".
Kirkus Review.
Publisher's Weekly.
School Library Journal.
1.5
K-3
Keywords: Counting -- Juvenile literature; Counting; Counting